Analysis of tangerine handling and marketing in Thailand - Chanpen Ampunpong; Tinsley, Richard L.; Athapol Noomhorm; Boonjit Titapiwatanakun; Hansen, Gunner K.; DANIDA, Denmark (Bangkok : Asian Institute of Technology, 1996)
This study was conducted in economic important area of tangerine. The study was focused on the performance of tangerine production, handling and marketing. Postharvest operation was conducted most at wholesale market. It was emphasized on grading, sorting and degreening which help the marketing of tangerine. Postharvest losses increase if the handling system is more complex and highest at retail outlet (5%). Degreening operation is important to promote the good acceptable yellow color but also induces weight losses (2.3%). Cost of pesticide, labor and fertilizer are the major variable cost (79%) of tangerine production. Marketing cost are high at wholesale and retail outlet due to postharvest activities and cost of container. Plastic crates was much accepted throughout the system as it have various advantages as well as can reduce loss of damaged fruit. However, it contributes a significant share in marketing cost due to it high investment cost and losses of container (21 % at collecting point, 23% at wholesale level). The produce distribution and marketing system of tangerine have much developed at some level. However, there was no pricing system like auction used in the wholesale market. The problems encounter the production and marketing is shortage of labor and high cost of production, the fluctuation in price and high marketing cost. Therefore, there is the needs in more efficient reducing every handling losses which occurred in the system. Some postharvest operation like waxing, disinfastation are needs in case the expansion of exportation.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1996
Keywords: Tangerine -- Thailand; Tangerine -- Marketing